Determining the frequency of sacralization in patients with low back pain referred to MRI ward of Ali IbneAbitaleb Hospital in Zahedan - Hasan Ahmadi; Sharareh Sanei Sistani; Hamid Dahmardeh (فصلنامه ابن سینا)
Background and aims: One of the most common congenital spinal defects is sacralization and its correct and early diagnosis as an underlying factor will play an important role in the treatment and control of spinal disorders. Therefore, this study was designed to investigate the prevalence of sacralization in MRI of patients referred to Ali IbneAbitaleb Hospital in Zahedan city, Iran. Methods: In this prospective descriptive study, patients with low back pain referred to Ali IbneAbitalebHospital in Zahedan city in 2019 who underwent lumbosacral MRI were included. Data were collected using information form. Patients’ MRI was reviewed by a radiologist and the required information was extracted. Data were analyzed using SPSS software. Results: Totally, 500 patients including 189 men (37.8%) and 311 women (62.2%) were enrolled in the study. The mean age of the subjects was 41.0±13.7 years. In this study, sacralization was observed on MRI of 39 patients (7.8%), which was 9% in men and 7.1% in women. There was no significant difference between male and female in prevalence of sacralization. Conclusion:. Prevalence studies of the general population and  comparative studies with symptomatic patients is recomended.